Heavy Metal Contamination in Yogurt from Lebanon: Evaluating Lead (Pb) and Cadmium (Cd) Concentrations Across Multiple Regions - Sandra Sarkis; Rayan Kashmar; Nikolaos Tzenios; Maha Hoteit; Tony Tannous; Joseph Matta (Toxics)
The toxicity of metals such as lead (Pb) and cadmium (Cd) makes heavy metal contamination in food products a major health concern. The aim of this study is to measure the levels of Pb and Cd in yogurt samples that were collected from 11 distinct Lebanese locations and determine their compliance with the legal limits set by the European Commission (0.02 mg/kg for Pb and 0.005 mg/kg for Cd). A total of 165 yogurt samples were examined using atomic absorption spectrophotometry (AAS). Interestingly, the findings showed that 10.9% of samples had Pb concentrations over the allowable limit; the highest amounts were observed in Baalbeck-Hermel (0.118 mg/kg), North Area (0.125 mg/kg), and South Lebanon (0.115 mg/kg). In addition, the highest detected concentrations of Cd were found in North Area (0.094 mg/kg), Baalbeck-Hermel (0.076 mg/kg), and Akkar (0.042 mg/kg), with 14.5% of samples above the limit. The results show regional differences in contamination, which are probably caused by industrial emissions, agricultural activities, and environmental pollution. To better understand the potential health implications, the estimated daily intake (EDI) of Pb and Cd through yogurt consumption was calculated and compared to international health-based guidance values. Although the EDI values suggest a low risk from yogurt alone, the findings highlight the importance of cumulative exposure and emphasize the necessity of regular monitoring and stricter implementation of food safety laws to decrease exposure to heavy metals through dairy intake.